Effects of regulating international trade on firms and workers - Raymond Robertson (IZA World of Labor, 2018)
Economists have shown that international trade increases economic growth, with trade liberalization and integration having characterized the last 50 years. While trade can increase national welfare, recent estimates from both developed and developing countries show that labor market adjustment costs matter. Regulating trade, defined as adding or removing tariffs and other trade barriers, is not the best way to help lower-income workers who suffer from trade-induced losses. Policies that reduce adjustment costs may increase aggregate welfare more than regulating trade flows does.
Keywords: F1; F16; 330; regulation; international trade; adjustment costs; tariffs